28. COMPARISON OF THE STRUCTURE USING DOMESTIC MODERN PHARMACEUTICAL PRODUCTS WITHIN HEALTH INSURANCE COVERAGE IN PUBLIC HOSPITALS IN THE IMPLEMENTATION OF CIRCULAR 10/2016/TT-BYT PERIOD 2017-2019 (Vietnam Journal of Community Medicine, 2023)
Objective: Compare the change in the number of drug items, and the value of domestic drugmoney accounted for during the implementation of Circular 10/2016/TT-BYT at Vietnamese publichospitals, period 2017 - 2019.Subjects and methods: Policy analysis research. The subject was the list of modern pharmaceuticalsunder the payment scope of the Health Insurance fund used at public hospitals 3 times in 2017, 2018,and 2019.Result: The value of domestic drug money accounted in Circula 10 in 2018 and 2019 was higherthan in 2017 at all hospital lines as well as at each hospital level. The number of domestic drugitems in Circular 10 in 2018 and 2019 increased compared to 2017 in groups 2, 3, and 4 generic, ofwhich group 3 generic had the highest number of domestic drug items in Circular 10 in the 2017-2019 period.Conclusion: Circular 10 has had a specific impact in promoting substituting some foreign drugs withdomestic ones that meet the treatment requirements, drug prices, and supply capacity.
Keywords: Circular 10, Domestic drugs, public hospital.